The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ndt.s268582
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychometric Analysis of the Perceived Stress Scale Among Healthy University Students</p>

Abstract: Background: There is a gradual increase in the prevalence of stress during professional courses. Previous studies reported a high incidence of stress among university students. The psychometric properties of the perceived stress scale-10 (PSS-10) have been established in different populations. The current study aimed to assess psychometric properties of the PSS-10 in Saudi university students. Methods: Healthy university students (n= 192) participated in this cross-sectional study. All the participants were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 51 publications
(84 reference statements)
8
32
2
Order By: Relevance
“…The baseline levels of stress and anxiety among our participants were significantly higher than those found in the same population of university students by previous research [42][43][44], as well as in the general population [45]. Previous studies analyzing the mental health of university students found lower levels of anxiety and stress symptoms, evaluated through the GAD-7 and the PSS-10 questionnaires, compared to those of our sample of university students [42][43][44]. This is not surprising, since the COVID-19 pandemic had a worsening effect on the general population and on university students in particular: a research study conducted on Italian university students to identify psychological consequences of the living conditions during the COVID-19 lockdown reported high levels of anxiety and stress, concentration disorders, psychosomatization, and, in several cases, reactivation of trauma and worsened sleep quality [46].…”
Section: Principal Findingscontrasting
confidence: 84%
See 1 more Smart Citation
“…The baseline levels of stress and anxiety among our participants were significantly higher than those found in the same population of university students by previous research [42][43][44], as well as in the general population [45]. Previous studies analyzing the mental health of university students found lower levels of anxiety and stress symptoms, evaluated through the GAD-7 and the PSS-10 questionnaires, compared to those of our sample of university students [42][43][44]. This is not surprising, since the COVID-19 pandemic had a worsening effect on the general population and on university students in particular: a research study conducted on Italian university students to identify psychological consequences of the living conditions during the COVID-19 lockdown reported high levels of anxiety and stress, concentration disorders, psychosomatization, and, in several cases, reactivation of trauma and worsened sleep quality [46].…”
Section: Principal Findingscontrasting
confidence: 84%
“…The baseline levels of stress and anxiety among our participants were significantly higher than those found in the same population of university students by previous research [42][43][44], as well as in the general population [45]. Previous studies analyzing the mental health of university students found lower levels of anxiety and stress symptoms, evaluated through the GAD-7 and the PSS-10 questionnaires, compared to those of our sample of university students [42][43][44].…”
Section: Principal Findingscontrasting
confidence: 83%
“…The scale to assess the perceived stress scale of the studied sample was reliable with Cronbach's alpha coefficient 0. 78 as reported by (Anwer et al, 2020).…”
Section: Reliabilitymentioning
confidence: 56%
“… 13 A recent study on university students in Saudi Arabia found an adequate internal consistency of the PSS-10 as measured by Cronbach’s alpha of 0.78 and 0.71 for the PSS Factor-1 and Factor-2 scores, respectively. 16 …”
Section: Methodsmentioning
confidence: 99%